A fucoidan from sea cucumber Pearsonothuria graeffei with well-repeated structure alleviates gut microbiota dysbiosis and metabolic syndromes in HFD-fed mice. Issue 10 (28th September 2018) - Li, Shan; Li, Junhui; Mao, Guizhu; Wu, Tiantian; Hu, Yaqin; Ye, Xingqian; Tian, Ding; Linhardt, Robert J.; Chen, Shiguo
Abstract : A high-fat diet (HFD) has been a major contributor to increasing morbidity caused by metabolic syndromes. Abstract : A high-fat diet (HFD) has been a major contributor to increasing morbidity caused by metabolic syndromes. Functional foods from natural sources are potential choices for addressing metabolic diseases because they provide many health benefits with a low level of adverse side effects. In our former reports, fucoidan from Pearsonothuria graeffei (fuc- Pg ), a type of sulfated polysaccharides with a repeating structure, was shown to be a potential functional food ingredient. In this work, we investigated the effects of fuc- Pg on gut microbiota dysbiosis and metabolic syndromes caused by HFD. Our results indicated that fuc- Pg could reduce weight gains, alleviate hyperlipidemia, and protect the liver from steatosis in HFD-fed mice. Meanwhile, fuc- Pg decreases serum inflammatory cytokines and reduces macrophages infiltrating into adipose tissue. The gut microbiota dysbiosis caused by HFD was alleviated by administration of fuc- Pg, mainly working in the colon. Fuc- Pg increased abundances of Bacteroidetes and Actinobacteria while decreased Firmicutes and Proteobacteria. Our results indicated that fuc- Pg could be a functional food for gut microbiota dysbiosis and metabolic syndromes.